Animals can tell us more. (2nd September 2015) - Sachser, Norbert; Richter, S. Helene
Abstract: From a behavioural biologist's point of view, we argue: (1) The study of resilience in animals should not be restricted to neuronal mechanisms. Rather, questions of ontogeny, function, and evolution also should be addressed to achieve a comprehensive understanding. (2) Implementing new paradigms from animal welfare research in studies of resilience would allow an assessment of appraisal styles in animals.